Community Structure of Gastropod in Bahowo Mangrove Ecotourism Area - Handayani, Maymanah; Rangan, Jety K.; Lumingas, Lawrence J. L.; Manginsela, Fransine B.; Kepel, Rene C.; Ompi, Medy (Sam Ratulangi University, 2021)
This article describes the structure of the gastropod community in the Bahowo Mangrove Ecotourism Area, Manado. From 30 sample units (squared) analyzed, obtained 185 individual gastropods belonging to 27 species with an average density of 6.17 individuals/m2. The Shannon index value (H') is quite high at 3.038, the evenness index (E) is also high at 0.922, and the dominance index (D) is low at 0.078. This variation in gastropod community structure occurs between transects. In Transect 1 there are 15 species with an average density of 7.6 individuals/m2. The most dominant species in this transect was Tectus fenestratus with a density of 1.6 individuals/m2 and a relative abundance of 21.05%. In Transect 2 there are 7 species with an average density of 2.6 individuals/m2. The most dominant species in this transect was Angaria delphinus with a density of 0.6 individuals/m2 and a relative abundance of 23.08%. On Transect 3 there are 9 species with an average density of 8.3 individuals/m2. The most dominant species in this transect was Terebralia sulcata with a density of 2.7 individuals/m2 and a relative abundance of 32.53%. Compared to the other two transects, Transect 2 had lower individual abundance and density, but also the poorest species richness. In terms of biodiversity, Transect 1 is the highest. With a composition of 15 species, Transect 1 has a higher H' index value than in Transect 2 and Transect 3. Between Transect 2 and Transect 3 there is no significant difference in the Shannon index value. The three transects showed a low dominance index value and a relatively high evenness index value.Keywords: Gastropod; Community; Mangrove; Bahowo AbstrakArtikel ini menggambarkan struktur komunitas Gastropoda di Kawasan Ekowisata Mangrove Bahowo, Manado. Dari 30 unit sampel (kuadrat) yang dianalisis, diperoleh 185 individu gastropoda yang termasuk dalam 27 spesies dengan rata-rata kepadatan 6,17 individu/m2. Diperoleh nilai indeks Shannon (H’) cukup tinggi yakni 3,038, indeks kemerataan (E) juga tinggi yakni 0,922, dan indeks dominansi (D) yang rendah yakni 0,078. Variasi stuktur komunitas Gastropoda ini terjadi antar transek. Pada Transek 1 terdapat 15 spesies dengan kepadatan rata-rata 7,6 individu/m2. Spesies paling dominan di transek ini adalah Tectus fenestratus dengan kepadatan 1,6 individu/m2 dan kelimpahan relatif 21,05%. Pada Transek 2 terdapat 7 spesies dengan kepadatan rata-rata 2,6 individu/m2. Spesies paling dominan di transek ini adalah Angaria delphinus dengan kepadatan 0,6 individu/m2 dan kelimpahan relatif 23,08%. Pada Transek 3 terdapat 9 spesies dengan kepadatan rata-rata 8,3 individu/m2. Spesies paling dominan di transek ini adalah Terebralia sulcata dengan kepadatan 2,7 individu/m2 dan kelimpahan relatif 32,53% Dibandingkan dengan dua transek lainnya, Transek 2 memiliki kelimpahan dan kepadatan individu lebih rendah, tapi juga paling miskin kekayaan spesies. Dari segi keanekaagaman hayati, Transek 1 adalah yang tertinggi. dengan komposisi 15 spesies, Transek 1 memiliki nilai indeks H’ lebih tinggi dibandingkan dengan di Transek 2 dan di Transek 3. Antara Transek 2 dan Transek 3 tidak menunjukkan perbedaan yang nyata nilai indeks Shannonnya. Pada ketiga transek menunjukkan nilai indeks dominansi yang rendah dan nilai indeks kemerataan yang relatif tinggi.Kata Kunci: Komunitas; Gastropoda; Mangrove; Bahowo